1995
DOI: 10.1089/hyb.1995.14.9
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Approach for the Expression of High-Affinity Human Anti-Human Immunodeficiency Virus Immunoglobulin Fab Domains inEscherichia coli

Abstract: We describe here a two-phase approach for the development of high-affinity human anti-HIV immunoglobulin Fab domains in a bacterial expression system. The first phase of this technique involves the generation of human hybridoma cell lines producing high-affinity antibodies (MAbs). Anti-HIV-1 human MAbs from peripheral blood lymphocytes (PBLs) were prepared from an HIV-1-seropositive patient and from an HIV-1-seronegative volunteer immunized with HIV-1 rgp160. One MAb (T15G1), derived from the blood of the sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The mAb derived from one of these hybridomas displays high affinity binding to the cluster II determinant of the ectodomain of gp41 with a K d value of 4 ϫ 10 Ϫ10 M (20). This human anti-gp41 Ab or its recombinant Fab or single-chain fragment variable region (scFv) 3 have been repeatedly shown to bind to HIV-1 gp160 or gp41, but fail to block viral entry (20,21). Thus, it is truly a nonneutralizing Ab.…”
mentioning
confidence: 99%
“…The mAb derived from one of these hybridomas displays high affinity binding to the cluster II determinant of the ectodomain of gp41 with a K d value of 4 ϫ 10 Ϫ10 M (20). This human anti-gp41 Ab or its recombinant Fab or single-chain fragment variable region (scFv) 3 have been repeatedly shown to bind to HIV-1 gp160 or gp41, but fail to block viral entry (20,21). Thus, it is truly a nonneutralizing Ab.…”
mentioning
confidence: 99%
“…Moreover, anti-V1/V2 loop GPI-HCDR3 PG9 and PG16 have potent and broad neutralization activities similar to those of the soluble whole antibodies PG9 and PG16 (26,28,46). Furthermore, anti-C-helix GPI-scFv TG15 exhibited moderate neutralization against 8 out of 12 HIV-1 strains tested, whereas soluble whole antibody TG15, which was originally defined as a nonneutralizing antibody, does not have any neutralization activity (27,48). Finally, anti-MPER GPI-scFv 4E10 significantly increases neutralization potency compared to that of soluble whole antibody 4E10 (27,46,50).…”
Section: Discussionmentioning
confidence: 96%
“…This may block further conformational change of the HIV-1 envelope protein, thereby preventing HIV-1 envelopemediated membrane fusion and virus entry. Table 2 summarizes neutralization breadth and potency of GPI-anchored antibody derivatives (scFv, HCDR3, and VHH) that we have developed in this study or previous studies (26)(27)(28) compared to those of soluble whole antibodies, scFvs and VHHs, that serve as sources for GPI-anchored antibody derivatives (2,(45)(46)(47)(48)(49)(50). GPI-anchored antibody derivatives that we have tested include CD4BS, coreceptor-binding site (CRBS), V1/V2 loop, Chelix, and MPER antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The monoclonal antibody (TG15) derived from one of these hybridomas exhibits high affinity binding to the ectodomain of gp41 with a K d value of 4 ϫ 10 Ϫ10 M. 9 Using a competition assay by a panel of monoclonal antibodies with known specificity, it was found that only antibodies against cluster determinant II of gp41 can compete the binding of antibody (TG15) to HIV-1 envelope protein. This human monoclonal antibody and its recombinant Fab or scFv have been repeatedly shown to bind to HIV-1 gp160 or gp41, but fail to block viral entry.…”
Section: Introduction D Endritic Cells (Dcs) Express Toll-like Receptmentioning
confidence: 99%
“…This human monoclonal antibody and its recombinant Fab or scFv have been repeatedly shown to bind to HIV-1 gp160 or gp41, but fail to block viral entry. 9,10 Thus, it is a true nonneutralizing antibody.…”
Section: Introduction D Endritic Cells (Dcs) Express Toll-like Receptmentioning
confidence: 99%